Moving on from Permanent Supportive Housing: Facilitating Factors and Barriers among People with Histories of Homelessness. Issue 2 (April 2017) - Livingstone, Kimberly R.; Herman, Daniel B.
This study explored factors promoting and impeding formerly homeless permanent supportive housing tenants from moving into more independent community housing. Interviews were conducted with 10 current and 11 former residents. Facilitators included support received during supportive housing tenure, a focus on set goals, supportive housing as a stepping-stone, and a willingness to fight for what they hope to accomplish. Barriers included lack of affordability and rental assistance, fear of becoming homeless again, unacceptability of available housing, and limited help facilitating the transition. Permanent supportive housing residents may benefit from expanded use of support received during tenure. Affordability will likely remain a barrier. Given federal disinvestment in rental subsidies, growth in locally funded programs and other strategies will likely be required.